The impact of crisis communication in social media on netizen behaviour: A case study of Zus coffee crisis - Gan, Ka Yee; Mah, Pei Bao; Ooi, June Chi; Tung, Jye Yi; Wong, Zhi Seng (2023)
The population of social media users in Malaysia increased by 2.3 million, which accounts for approximately 8% of the population, between 2021 and 2022. Nowadays, dissatisfied customers often express their grievances and seek retribution on social media when they feel mistreated or ignored by organisations. However, this phenomenon has negative implications and can potentially lead to significant social media crises. Therefore, effective crisis communication is crucial for organisations. Nevertheless, many organisations frequently fail to implement the best crisis response strategies during the crisis, which could damage their reputation. In this research, an inductive qualitative approach will be used to identify the organisation’s crisis response and crisis response strategies during a crisis, and to investigate the impact of an organisation’s crisis communication in social media on netizen behaviour. Purposive sampling method will be applied to select the sample of crisis response and crisis response strategies, where three statements posted by ZUS Coffee on Facebook will be selected as sample to analyse. Besides, a simple random sampling method will be applied to collect data on netizens’ behaviour, where a total of 1,000 Facebook comments from netizens under the statements of ZUS Coffee will be selected using simple random sampling methods. Content analysis will be used to analyse the data collected. The findings revealed that the most used of crisis response by ZUS Coffee is meeting the public’s communication needs and the most used of crisis response strategy is corrective action. However, the impact of ZUS Coffee’s crisis communication on netizen behaviour on social media was predominantly negative. The discussion draws on relevant journal studies and there are some similarities and differences compared to the other studies.